2000
DOI: 10.1111/1469-8986.3720224
|View full text |Cite
|
Sign up to set email alerts
|

Discrete and continuous prepulses have differential effects on startle prepulse inhibition and skin conductance orienting

Abstract: The effectiveness of different types of auditory prepulses in eliciting skin conductance orienting and in producing prepulse inhibition (PPI) of the acoustic startle eyeblink was studied in two experiments. A discrete white noise prepulse produced greater PPI than either a continuous white noise, a discrete tone, or a continuous tone. The discrete white noise advantage was not due to similarity in bandwidth to the startle pulse or to a refractory effect of the prepulse. Moreover, a dissociation between PPI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…This same non-linear relationship between prestimulus salience and perceptual intensity has been demonstrated with prepulse effects on pain (Blumenthal et al, 2001), and indeed, with prepulse effects on startle magnitude . Also, activation of both inhibitory and summation processes by prepulses in a prepulse-startle paradigm has been shown (Blumenthal & Levey, 1989;Wynn et al, 2000), with inhibition due to the onset transient aspects of the prepulse, and summation based on the steady-state body of the prepulse (increasing with increased duration, as in the PPIPSI finding of the present study).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This same non-linear relationship between prestimulus salience and perceptual intensity has been demonstrated with prepulse effects on pain (Blumenthal et al, 2001), and indeed, with prepulse effects on startle magnitude . Also, activation of both inhibitory and summation processes by prepulses in a prepulse-startle paradigm has been shown (Blumenthal & Levey, 1989;Wynn et al, 2000), with inhibition due to the onset transient aspects of the prepulse, and summation based on the steady-state body of the prepulse (increasing with increased duration, as in the PPIPSI finding of the present study).…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, we assessed the relationship between PPIPSI and prepulse intensity, duration, and bandwidth. To the extent that PPIPSI provides information similar to that found with PPI of startle, we expected increased PPIPSI as prepulse intensity or duration increased to some asymptote (Blumenthal, 1995(Blumenthal, ,1996, and greater PPIPSI with broadband noise prepulses than with pure tone prepulses (Wynn et al, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Discrete white noise prepulses were previously shown to produce significantly more PPI than either a discrete tone, a continuous tone, or a continuous white noise [19]. Similarly, Braff et al [13] reported that discrete white noise prepulses were most effective in eliciting PPI, and that this type of prepulse resulted in more pronounced PPI differences between normal control subjects and PPI-deficient clinical populations.…”
Section: Discussionmentioning
confidence: 95%
“…17 17 During the last 2 decades, SC-OR has been frequently used to determine the OR component of a so-called prepulse, which has been applied to modify the human startle eyeblink reflex (Filion, Dawson, & Schell, 1998). Such a stimulus either terminates before, or continues up to, and sometimes beyond the startle stimulus (Wynn, Dawson, & Schell, 2000). It was hypothesized that a prolonged prepulse may elicit a generalized OR (Sect.…”
Section: Differentiation Between Orienting Defensive and Startle Rementioning
confidence: 99%